#22 Phytochemical investigation and in-vitro antioxidant activity of Memecylon umbellatum using DPPH method - KS, Chandrashekar; Chaudhary, Shilpee (Journal of Pharmaceutical Chemistry, 2022)
Memecylon umellatum Burm. (Synonym. Memecylon edule) belongs to the family Melastomataceae. It is a larges ornamental shrub or small tree found in the coastal region of deccan peninsula and eastern parts of India. The leaves of Memecylon umbellatum have been used traditionally to treat various infection and inflammatory conditions. The plant is the richest source of flavonoids and terpenoids which are known for anticancer activity. The present study was undertaken to isolate the phytoconstituents from ethyl acetate extract and to screen the antioxidant activity from the leaves of Memecylon umbellatum. Phytochemical investigation was carried out using column chromatographic technique and in-vitro antioxidant activity was evaluated using DPPH (1, 1-diphenyl-2-picryl hydrazyl) free radical scavenging assay. The chemical investigation of the leaves of Memecylon umbellatum led to the isolation of quercetin, pyrogallol, and gallic acid from ethyl acetate extract by successive extraction with different solvents and using column chromatography. These constituents were characterized by IR, 1H-NMR, 13C-NMR, and Mass spectral analysis. The ethyl acetate extract showed significant antioxidant activity. From the pharmacological studies carried out, it is evident that ethyl acetate extract of Memecylon umbellatum endowed significant antioxidant activity. The antioxidant activity may be due to quercetin, pyrogallol, and gallic acid. These constituents were isolated for the first time from this plant.
Keywords: aaa